Combined Kidney-Liver, Heart-Liver, and Kidney-Pancreas Transplantations from a Single Deceased Donor. (11th October 2012) - Ravaioli, Matteo; Serenari, Matteo; Cescon, Matteo; Martin Suarez, Sofia; Cucchetti, Alessandro; Ercolani, Giorgio; Del Gaudio, Massimo; Catena, Fausto; Morelli, Cristina; Arpesella, Giorgio; Pinna, Antonio Daniele
Abstract : Splitting the liver for two adults to increase the donor pool is still a debated issue, especially for combined organ transplantation. We described a case of liver-splitting procedure for two adults, which was successful even in the presence of combined organ transplantation. Three adult combined organ transplantations from one deceased donor were performed, with, use of split liver grafts in two patients: a combined heart-right split liver, a left kidney-left split liver, and a right kidney-pancreas transplantation. Despite a not perfect match between the graft type and recipient, the prevention of small-for-size syndrome by ligature of the splenic artery, and/or hemiportocaval shunt in the patient receiving the left split liver, and the maximal reduction of ischemia time were the main factors contributing to the success of the procedure. This is the first report of combined heart and split liver in two adults which may suggest new strategies for organ transplantations.